A Methodology to Regulate Transformation of a City’s Appearance Due to Energy Efficiency Building Renovations: A Case Study: Errenteria (Spain) - Iñigo Lizundia; Eneko Jokin Uranga; Leire Azcona (Heritage, 2023)
The need to improve the energy performance of European buildings is beyond all doubt, as indicated by the different regulatory determinations on energy and climate change adopted by different public administrations in recent years. The primary actions have focused on improving the thermal enclosure of buildings; the placement of new energy-efficient skins on their exterior façades is consequently beginning to deconfigure, distort, homogenize and globalize the city in an alarming manner. In the case of Spain, the lack of a specific regulation on how to proceed when renovating the vast majority of residential buildings without heritage protection is leaving the ultimate decision in the hands of owner associations. It is therefore urgent to endow municipal administrations with a tool enabling them to regulate and control the transformation of a city’s image before it is too late. To that end, a pioneer methodology is proposed to classify the unprotected building stock of a municipality with a view to future renovation actions, depending on the degree of their vulnerability and the greater or lesser need to protect their image and the other pre-existing features. As a theoretical case study to test the proposed methodology, the locality of Errenteria, Spain, was chosen, demonstrating that it is an effective tool easy to apply in any city nationwide, regardless of the respective location, size and management capacity.